A novel colorimetric and ratiometric fluorescent probe for sensing SO2 derivatives and their bio-imaging in living cells. Issue 5 (15th January 2019) - Niu, Tingting; Yu, Ting; Yin, Guoxing; Chen, Haimin; Yin, Peng; Li, Haitao
Abstract : We report a novel fluorescent probe HBN–TCF for the detection of SO2 derivatives. Abstract : We report a novel fluorescent probe HBN–TCF for the detection of SO2 derivatives. This probe exhibited near-infrared fluorescence emission with an excitation wavelength of 620 nm. After reacting with SO3 2−, the emission channel at 664 nm decreased, while the new strong emission channel at 482 nm increased ( λ ex = 400 nm), with a large emission distance (Δ λ = 182 nm) observed. This probe exhibited the rapid and selective detection of SO2 derivatives compared with other sulfur-containing species and featured a low detection limit (82 nM). This colorimetric and ratiometric fluorescent probe showed high selectivity and sensitivity for detecting SO2 derivatives. The probe was also successfully exploited for the fluorescence imaging of intracellular and exogenous SO2 derivatives in BEL-7402 cells.